Risk profiling of 3-MCPD (3-monochloropropane-1,2-diol) in soy sauce to the adult Filipino consuming population - Rustia, Abigail S.; Bulagao, Bebviet Franz R.; Bautista, Karina Angela D.; Mahoney, Deon; Villarino, Casiana Blanca J.; Barrios, Erniel B.; Capanzana, Mario V. (2021)
"Soy sauce is one of the commonly consumed food items in the Philippines because of its vast applications as a regular sauce and a condiment in various food dishes. One method used to produce soy sauce is chemical hydrolysis that involves acid hydrolysis of vegetable protein under high temperatures, which may generate a chemical by-product called 3-monochloropropane-1,2-diol (3-MCPD). Exposure to 3-MCPD may potentially cause adverse health effects to humans such as kidney, liver, and reproductive organ failure, as well as infertility and carcinogenicity. -Title page.
Includes bibliographical references.
Keywords: Soy sauce -- Philippines; Risk assessment -- Philippines; Cooking (Soy sauce) -- Philippines